2020
DOI: 10.47197/retos.v38i38.77625
|View full text |Cite
|
Sign up to set email alerts
|

Do differences between the training load perceived by elite beach volleyball players and that planned by coaches affect neuromuscular function? (¿Las diferencias entre la carga de entrenamiento percibida por los jugadores de voleibol de playa de élite y

Abstract: Summary. This study aimed to verify the differences between the training load planned by coaches and that perceived by Beach Volleyball (BV) players and observe the effects on athletes’ neuromuscular function. Three female BV players and well-known coaches participated in the research and were accompanied for three training weeks in the preseason phase. Rating of perceived exertion (RPE) was collected through the 0-10 scale during a previous training session. Strength, physical fitness and tactical-technical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Beach volleyball is a team sport characterized by its intermittent nature, fluctuating randomly from short periods of maximal or sub-maximal activity to long periods of moderate and low-intensity activity ( Arruda & Hespanhol, 2008 ; Magalhães et al, 2011 ; Medeiros et al, 2014 ). This alternating activity nature arise in game actions as jumps, constituting one of the most determining physical-technical elements in beach volleyball performance ( Andrade et al, 2020 ; Medeiros et al, 2014 , 2023 ; Oliveira et al, 2018 ). Accordingly, literature within beach volleyball scope has pointed out that jump measures can help coaches monitor training load and understand the activity profile of players ( Andrade et al, 2020 ; Medeiros et al, 2023 ; Oliveira et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beach volleyball is a team sport characterized by its intermittent nature, fluctuating randomly from short periods of maximal or sub-maximal activity to long periods of moderate and low-intensity activity ( Arruda & Hespanhol, 2008 ; Magalhães et al, 2011 ; Medeiros et al, 2014 ). This alternating activity nature arise in game actions as jumps, constituting one of the most determining physical-technical elements in beach volleyball performance ( Andrade et al, 2020 ; Medeiros et al, 2014 , 2023 ; Oliveira et al, 2018 ). Accordingly, literature within beach volleyball scope has pointed out that jump measures can help coaches monitor training load and understand the activity profile of players ( Andrade et al, 2020 ; Medeiros et al, 2023 ; Oliveira et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This alternating activity nature arise in game actions as jumps, constituting one of the most determining physical-technical elements in beach volleyball performance ( Andrade et al, 2020 ; Medeiros et al, 2014 , 2023 ; Oliveira et al, 2018 ). Accordingly, literature within beach volleyball scope has pointed out that jump measures can help coaches monitor training load and understand the activity profile of players ( Andrade et al, 2020 ; Medeiros et al, 2023 ; Oliveira et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, researchers have been conducting research on the factors that affect athletes' performance and match outcomes. Previously, some important studies have contributed to the increase in the knowledge of the physiological response [1,2], technical and tactical aspects [3], training load [4][5][6], and match analysis of BV [7][8][9]. Most of the findings revealed that BV is performed intermittently, with brief bouts of high-intensity exercise interspersed by low-intensity periods [10].…”
Section: Introductionmentioning
confidence: 99%
“…The success of the training process and, consequently, of volleyball matches depends on adjustments that balance the magnitude and distribution of training load and recovery [ 12 , 16 ]. Positive relationships were observed between performance in game actions that require powerful vertical jumps (serving, blocking, and attacking) and overall success in matches [ 14 ].…”
Section: Introductionmentioning
confidence: 99%